Rockfall Risk Assessment and Open-cut Tunnel Safety Evaluation at Railway Tunnel Portal Based on 3D Kinematic Simulation - Tian, Haoran (Journal of Progress in Civil Engineering, 2025)
To assess the rockfall risk at railway tunnel portals, this study proposes an integrated risk assessment methodology combining three-dimensional kinematic simulation and structural safety analysis. Taking a railway tunnel portal project as a case study, field investigations, UAV oblique photogrammetry, and laboratory-field tests were conducted to obtain rockfall distribution and geological data. A 3D reality-based model was established to characterize rock mass features. Three-dimensional kinematic simulations using Rockfall Hunter software were performed on representative rockfalls to analyze post-failure trajectories and impact energy on the Open-cut Tunnel structure. The structural safety of the Open-cut Tunnel was evaluated through finite element analysis. The results demonstrate that Rockfall W5 at Tunnel Portal I exhibits high collapse risk with maximum impact energy reaching 335.61 kJ, potentially causing direct effects on the Open-cut Tunnel structure. However, under current reinforcement conditions, the Open-cut Tunnel structure effectively resists impact loads, meeting structural safety requirements. Comprehensive analysis suggests prioritized risk control measures at Tunnel Portal I, where enhanced monitoring and protective measures are crucial for ensuring railway operational safety.